Can Debt Relief Boost Growth in Poor Countries? - Nguyen, Toan (Economic Issues; Economic Issues ;, 2007)
The Heavily Indebted Poor Countries (HIPC) Initiative, launched in 1999 by the IMF and the World Bank, was the first coordinated effort by the international financial community to reduce the foreign debt of the world's poorest countries. It was based on the theory that economic growth in heavily indebted poor countries was being stifled by heavy debt burdens, making it virtually impossible for these countries to escape poverty. However, most of the empirical research on the effects of debt on growth has lumped together a diverse group of countries, and the literature on the countries' impact of debt on poor is scant. This pamphlet presents the findings of the authors' empirical research into the subject, analyzing the channels through which debt affects growth in low-income countries.